2022
DOI: 10.1136/bcr-2022-249610
|View full text |Cite
|
Sign up to set email alerts
|

Massive lung necrosis due to microwave ablation in an octogenarian required urgent lobectomy

Abstract: We present a rare complication of microwave ablation (MWA) in a male patient in his 80s. His massive pulmonary necrosis and tension pneumothorax required urgent surgery. However, the damage to the lung tissue was too large, deep and fragile. We failed to suture or conduct wedge resection on the lung lesion, so, left upper lobectomy was necessary. Therefore, we suggest that it is probably possible to reduce the frequency and time threshold when performing MWA for the elderly with comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The only reported case of massive lung necrosis after MWA involved an elderly male patient in his 80s diagnosed with lung squamous cell carcinoma [ 5 ]. On the fourth day post-MWA, the development of pneumothorax and dyspnea and failure to manage the symptoms resulted in an urgent left upper lobectomy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only reported case of massive lung necrosis after MWA involved an elderly male patient in his 80s diagnosed with lung squamous cell carcinoma [ 5 ]. On the fourth day post-MWA, the development of pneumothorax and dyspnea and failure to manage the symptoms resulted in an urgent left upper lobectomy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only reported case of massive lung necrosis after MWA involved an elderly male patient in his 80s diagnosed with lung squamous cell carcinoma [ 5 ]. On the fourth day post-MWA, the development of pneumothorax and dyspnea and failure to manage the symptoms resulted in an urgent left upper lobectomy [ 5 ]. The authors suggested that the elastic properties of the lung tissue in the elderly are more fragile, requiring a reduced frequency and time threshold when performing MWA in this population [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation